LAT1 expression in head and neck cancer: a prognostic biomarker with potential relevance for BNCT - Cavalieri, Stefano; Nuzzolese, Imperia; Lenoci, Deborah; Lucchetta, Marta; Ficorilli, Marica; Orlandi, Ester; De Cecco, Loris; Licitra, Lisa (Frontiers in Oncology, 2025)
PurposeThe increased expression of LAT1, an amino acid transporter, in cancer cells makes boronophenylalanine (BPA) uptake higher in cancer vs. healthy tissues: a high LAT1 expression on cancer cells implies a higher sensitivity to boron neutron capture therapy (BNCT). We explored the LAT1 expression in a cohort of head and neck cancer (HNSCC) patients, stratifying them according to a previously published transcriptomic 6-cluster model.MethodsWe analyzed 100 HNSCC patients treated with multimodal treatments including radiotherapy. Transcriptomics of primary tumor specimens was obtained by Affymetrix ClariomD chips and processed using the Transcriptome Analysis Console Software (ThermoFisher). We retrieved normalized and log2 LAT1 from the data matrix. Data were used to analyze: i) the distribution by anatomical subsites and transcriptomic subtypes (assessed by Kruskal-Wallis test); ii) overall survival (OS).ResultsLAT1 expression was high (>2.83) in 13% of cases. At median follow-up of 64.44 months (95% CI: 54.24-66.91), overall median OS was 94.24 months, 22.99 months (95% CI 14.31-NR) in patients with high LAT1 vs. 94.24 months (95% CI 65.1-NR) in those with low LAT1. LAT1 expression did not differ significantly among HNSCC primary sites. Among GE clusters, the highest LAT1 expression was observed in those with the worst prognosis, the lowest in the immune-reactive one (p=.000028).ConclusionHigh LAT1 expression has a negative prognostic role and is associated with transcriptomic clusters with unfavorable and radioresistant biologic features. These results justify the use of BNCT in radioresistant HNSCCs and may guide patient selection for future clinical studies with BNCT.